Fish-farming in Sub-Saharan Africa - profits waiting to be netted - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Fish-farming in sub-Saharan Africa, case studies in the francophone countries - proposals for future action, research report by Jerome Lazard, Yves Lecompte, Bozena Stomal and Jean-Yves Weige ISBN 211 086732 9 Price 120ff Distributed by AGRIDOC Intern